The Offshore Renminbi Exchange Rate: Microstructure and Links to the Onshore Market - Yin-Wong Cheung; Dagfinn Rime (Center for Economic Studies and ifo Institute (CESifo), 2014)
The offshore renminbi (CNH) exchange rate is the exchange rate of the Chinese currency transacted outside China. We study the CNH exchange rate dynamics and its links with onshore exchange rates. Using a specialized microstructure dataset, we find that CNH is significantly affected by its order flow and limit-order imbalance. The offshore CNH exchange rate has an increasing impact on the onshore rate, and significant predictive power for the official RMB central parity rate. The CNH order flow also affects the onshore RMB exchange rate and the central parity rate. The interactions between variables are likely to be time-varying.
Keywords: F31; F33; G14; G15; G21; G28; 330; foreign exchange market microstructure; order flow; limit-order imbalance; CNH; CNY; central parity rate